The pharmacokinetic study of rutin in rat plasma based on an electrochemically reduced graphene oxide modified sensor - Pei Zhang; Yu-Qiang Gou; Xia Gao; Rui-Bin Bai; Wen-Xia Chen; Bo-Lu Sun; Fang-Di Hu; Wang-Hong Zhao (Elsevier, 2016)
An electrochemical method based on a directly electrochemically reduced graphene oxide (ERGO) film coated on a glassy carbon electrode (GCE) was developed for the rapid and convenient determination of rutin in plasma. ERGO was modified on the surface of GCE by one-step electro-deposition method. Electrochemical behavior of rutin on ERGO/GCE indicated that rutin underwent a surface-controlled quasi-reversible process and the electrochemical parameters such as charge transfer coefficient (α), electron transfer number (n) and electrode reaction standard rate constant (ks) were 0.53, 2 and 3.4 s−1, respectively. The electrochemical sensor for rutin in plasma provided a wide linear response range of 4.70×10−7−1.25×10−5 M with the detection limit (s/n=3) of 1.84×10−8 M. The assay was successfully used to the pharmacokinetic study of rutin. The pharmacokinetic parameters such as elimination rate half-life (t1/2), area under curve (AUC), and plasma clearance (CL) were calculated to be 3.345±0.647 min, 5750±656.0 µg min/mL, and 5.891±0.458 mL/min/kg, respectively. The proposed method utilized a small sample volume of 10 μL and had no complicated sample pretreatment (without deproteinization), which was simple, eco-friendly, and time- and cost-efficient for rutin pharmacokinetic studies.